Controlling the size and shape of Mg-MOF-74 crystals to optimise film synthesis on alumina substrates - Campbell, James; Tokay, Begum (Elsevier, 2017)
Mg-MOF-74 is a metal organic framework with the highest CO2 adsorption capacity of any porous material. Therefore, it has been suggested for CO2 separations as both an adsorbent and incorporated into membranes. Design of the Mg-MOF-74 crystal morphology is important to expand the applicability of the material. In this paper one step synthesis of Mg-MOF-74 films has been achieved by controlling the Mg-MOF-74 crystal morphology. Results show that increasing the fraction of ethanol and water in the reaction solution relative to dimethyl formamide (DMF) increases the size of the crystals produced, while resulting in a subsequent drop in yield. By using solvent composition to control the Mg-MOF-74 crystal size and shape the synthesis of Mg-MOF-74 thin films was achieved in one step, without the need for seeding. Films could be produced as thin as 1 μm, ten times thinner than any other previous membranes in the M-MOF-74 series, in a fraction of the time (only 2.5 h). Thicker films (up to 14 μm) could also be produced by increasing the fraction of ethanol and water in reaction solution, offering a methodology by which the thickness of Mg-MOF-74 membranes can be controlled. Films were produced on porous tubular alumina supports, and single gas measurements were conducted resulting in a CO2 permeance of 7.4 × 10−7 mol m−2 s−1 Pa−1 and an ideal CO2/CH4 selectivity of 0.5.